KEBIJAKAN KEUANGAN DAN GOOD CORPORATE GOVERNANCE TERHADAP AGRESIVITAS PAJAK - Setyawan, Setu; Wahyuni, Endang Dwi; Juanda, Ahmad (Jurnal Reviu Akuntansi dan Keuangan)
This research aims to analyse the effect of financial policy and good corporate governance (GCG) on tax aggressiveness. Financial policies are prokated with leverage, capital intensity and inventory intensity. The GCG used are the institutional ownership, independent Board of Commissioners, audit committees and audit quality. The population is manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) period 2016-2017. Sampling method is used purposive sampling and obtained as much as 56 samples. Data analysis techniques use multiple linear regression using the SPSS 23. The results show that financial policies have an effect on tax aggressiveness. While the GCG on the independent Proxy Commissioner and Audit Committee has an effect on tax aggressiveness, while the other proxies are the ownership of the insitution and audit quality does not affect the aggressiveness of the tax.